2020
DOI: 10.1038/s41598-020-75529-0
|View full text |Cite
|
Sign up to set email alerts
|

Akt isoform-specific effects on thyroid cancer development and progression in a murine thyroid cancer model

Abstract: The Akt family is comprised of three unique homologous proteins with isoform-specific effects, but isoform-specific in vivo data are limited in follicular thyroid cancer (FTC), a PI3 kinase-driven tumor. Prior studies demonstrated that PI3K/Akt signaling is important in thyroid hormone receptor βPV/PV knock-in (PV) mice that develop metastatic thyroid cancer that most closely resembles FTC. To determine the roles of Akt isoforms in this model we crossed Akt1−/−, Akt2−/−, and Akt3−/− mice with PV mice. Over 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…AKT, a protein kinase that regulates cell survival and apoptosis, is phosphorylated by PDK1 ( 33 , 34 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AKT, a protein kinase that regulates cell survival and apoptosis, is phosphorylated by PDK1 ( 33 , 34 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Akt isoform specifically promoted the development of thyroid cancer in a mouse thyroid cancer model. 34 The PI3K/AKT pathway is one of the most critical molecular signaling pathways involved in key cellular processes of thyroid malignancies. 35 It has been reported that IRS proteins may become biomarkers of PI3K pathway activity and serve as necessary biomarkers to guide targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Akt isoform specifically promoted the development of thyroid cancer in a mouse thyroid cancer model 34 . The PI3K/AKT pathway is one of the most critical molecular signaling pathways involved in key cellular processes of thyroid malignancies 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Activating mutations in genes encoding these protein kinases have been detected in FTCs, PDTCs and ATCs [ 53 , 55 , 56 ]. Murine TC model-based studies have shown that AKT1 is the primary promoter of TC development and local invasion, while vascular invasion and metastatic progression are dependent predominantly on AKT1 and AKT3, and to a lesser extent, on AKT2 [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%